DETERMINING THE CAPACITY OF A CONTROLLING SHAREHOLDER IN A COMPANY - Radović, Mirjana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
In this article, the author analyses the capacity of a controlling shareholder of a limited liability company or a joint stock company under the provisions of the Serbian Law on Partnerships and Companies of 2011. The analysis is based on the current interpretation of the statutory provisions in domestic legal theory and practice, taking into account the understanding developed in comparative legal systems. After some introductory remarks on the importance of determining the capacity of a controlling shareholder, the second part of the paper explains the implicit statutory definition of a controlling shareholder. The third part is devoted to the presumption of the capacity of a controlling shareholder which applies to the shareholder with the majority of the voting rights at the general meeting. Contrary to the prevailing view in the literature, the author argues that this presumption is rebuttable and identifies the main grounds for rebuttal. The fourth part of the paper examines the possibility for a minority shareholder to become a controlling shareholder. In particular, the author focuses on minority control based on a de facto majority of votes in the general meeting, the combination of different means of control and acting in concert. Finally, the concluding part contains an overview of the most important suggestions for the correct interpretation of the legal provisions for determining the capacity of a controlling shareholder.